The Activity of Urolithin A and M4 Valerolactone, Colonic Microbiota Metabolites of Polyphenols, in a Prostate Cancer In Vitro Model - Stanisławska, Iwona J.; Granica, Sebastian; Piwowarski, Jakub P.; Szawkało, Joanna; Wiązecki, Krzysztof; Czarnocki, Zbigniew; Kiss, Anna K. (Planta Medica, 2019)
The gut microbiota-derived metabolites of ellagitannins and green tea catechins, urolithin A (uroA) and 5-(3′,4′,5′-trihydroxyphenyl)-γ-valerolactone (M4), respectively, are among the main compounds absorbed into human system after ingestion of these polyphenols. The aim of this study was to establish the effects of M4, uroA, and their combinations on LNCaP cells, an androgen dependent prostate cancer in vitro model.. The LNCaP cells were incubated with increasing concentrations of tested metabolites. The cell proliferation was determined by measurement of DNA-bisbenzimide H 33 258 complexes fluorescence. The isobolographic analysis was used to establish the type of interaction between metabolites. The apoptosis, androgen receptor (AR) localization, and phosphorylation of Akt kinase were measured by flow cytometry. Prostate-specific antigen (PSA) secretion was determined by ELISA. M4 showed modest antiproliferative activity in LNCaP cells (IC50 = 117 µM; CI: 81 – 154). UroA decreased proliferation (IC50 = 32.7 µM; CI: 24.3 – 41.1) and induced apoptosis of LNCaP cells. The mixture of M4 with uroA had synergistic antiproliferative effect. Moreover, M4 potentiated inhibition of PSA secretion and enhanced retention of AR in cytoplasm caused by uroA. Interestingly, uroA increased levels of pSer473 Akt in LNCaP cells. These results show that colonic metabolites may contribute to chemoprevention of prostate cancer by varied polyphenol-rich diet or composite polyphenol preparations.
Keywords: urolithin A; 5-(3′,4′,5′-trihydroxyphenyl)-γ-valerolactone; metabolization; microbiome; green tea; prostate cancer